Peran Implementasi Sistem Informasi Akuntansi Dalam Meningkatkan Strategi Bisnis UMKM di Probolinggo - Kinaza, Tsibat Vozi; Diana, Nur; Mawardi, M. Cholid (Universitas Islam Malang, 2023)
Identify and analyze UMKM in implementing accounting information systems to improve their business strategies in 6 (six) sub-districts of Probolinggo Regency. This study uses qualitative research with a phenomenological approach and uses primary data collection through the distribution of open and closed questionnaires to 55 owner UMKM in 6 (six) Districts of Probolinggo Regency and through direct interviews. With descriptive data analysis and Strengths Weakness, Opportunities, Threats (SWOT) analysis. Based on the results of research on 55 owner UMKM in 6 (six) Districts of Probolinggo Regency, most of the, still use and apply traditional management or manually in carrying out their financial reporting and lack of understanding of accounting information systems, therefore the business strategy is not appropriate to increase their business. The business strategy related to strengths and weaknesses of owner UMKM in Probolinggo Regency, the strengths factor is still implementing online strategies and the weakness is marketing access. However, the opportunity and threat factors are as follows, the opportunity is equitable development and the threat factor is rising raw material prices.Keywords : Accounting information system, business strategy, UMKM